Structure optimization system based on the bone surface adaptation phenomenon - Nowak, Michał; Morzyński, Marek (Computer Assisted Methods in Engineering and Science; Vol 13 No 4 (2006), 2022)
In the paper the structure optimization system based on the surface remodeling is presented. The base of algorithm formulation was the trabecular bone surface remodeling phenomenon leading to optimization of the trabecular net in the bone as well as the design with optimal stiffness principle. The closed system including Finite Element mesh generation, decision criterion for structure adaptation and Finite Element Analysis in parallel environment are presented. The issues concerning the use of the tool for the mechanical design are discussed. Some results of computations, using special prepared software are presented.